Análise proteômica de paracoccidioides sp. em condições de estresse osmótico - Rodrigues, Leandro Nascimento da Silva (2014)
The dimorphic fungus Paracoccidioides is the etiological agent of paracoccidioidomycosis, a systemic mycosis with high relevance for the public health in Brazil and other Latin American countries such as Colombia and Venezuela. Generally, microorganisms require responses to stress conditions to survive in response to environmental changes and pathogenic organisms, particularly, require an effective response even higher to react against host defences. Osmotic stress has been used as a model to study signal transduction and seems to cause many cellular adaptations, which include signal transduction pathways modification, protein expression alteration and cellular volume and size regulation. In this work we have evaluated the proteomic profile of yeast cells of Paracoccidioides sp. (Pb01) obtained in osmotic stress condition. Data describe an osmoadaptative response of this fungus when subjected to this treatment. Proteins involved in the synthesis of the cell wall components were modulated, evidencing a remodelling of the cell wall. In addition, it was also observed alterations on the energy metabolism, given that proteins of the pentose phosphate pathway were abundant while proteins of the glycolysis were less abundant under osmotic stress condition. In addition changes in amino acid metabolism were also observed; more clearly the degradation of amino acids such as leucine, isoleucine and valine was induced during osmotic stress. Hereupon, our study suggests that Paracoccidioides sp. (Pb01) present a vast osmoadaptative repertoire; comprising different proteins which act complementarily and that this response could be able to minimize the effects caused by osmotic stress.